2019
DOI: 10.18502/cmm.5.4.2149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Fusarium species complex isolated from clinical samples and its antifungal susceptibility patterns

Abstract: Background and Purpose: More than 300 Fusarium species are grouped into approximately 23 species complexes out of which around 70 are involved in human infections. The nomenclature of these species has undergone considerable changes in recent years. These species cause localized infections in individuals while inducing systemic infections mainly in immunocompromised patients. The present study was conducted to identify Fusarium species in clinical isolates by molecular methods and determine their in vitro mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In the present study, the in vitro activity of amphotericin B against all the isolates was more potent than other agents tested. This is consistent with the findings of most studies in which amphotericin B was found to have lower MICs in vitro compared to other antifungals [ 4 , 13 , 35 , 36 , 37 ]. As previously reported [ 10 , 31 , 38 ], the susceptibility of Fusarium to amphotericin B varied, depending on the species.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, the in vitro activity of amphotericin B against all the isolates was more potent than other agents tested. This is consistent with the findings of most studies in which amphotericin B was found to have lower MICs in vitro compared to other antifungals [ 4 , 13 , 35 , 36 , 37 ]. As previously reported [ 10 , 31 , 38 ], the susceptibility of Fusarium to amphotericin B varied, depending on the species.…”
Section: Discussionsupporting
confidence: 92%
“…Miltefosine in combination with voriconazole demonstrated synergy against three mucormycetes and one isolate of Scedosporium prolificans [25]. In our study, miltefosine showed good inhibitory activity against all Fusarium isolates with MIC values ranging from 0.25 to 4 µg/mL, making it more potent than voriconazole (0.125-16), itraconazole (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and caspofungin (0.125-8). The MIC values for miltefosine reported here are consistent with the 2 µg/mL value reported for Cryptococcus neoformans and Cryptococcus gatti, C. glabrata, C. krusei, C. albicans, A. fumigatus, and Trichophyton mentagrophytes with this drug [40][41][42][43].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…However, approximately 70 Fusarium spp. are related to infections that cause fusariosis in humans [11,12]. The rate of human fungal infections increases with the upward trend of immunocompromised population, leading to an increase in the morbidity and mortality rates due to fusariosis [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%